THE EFFECTS OF UNCONTROLLED EXTRACTIONS OF THE PERMANENT LOWER FIRST MOLARS ON THE PROGNOSIS OF SPONTANEOUS SPACE CLOSURE AND OCCLUSION - Akif Demirel; Melike Kiraz; Mustafa Aydınbelge; Şaziye Sarı (Cumhuriyet University, 2020)
Objectives: This cross-sectional study aimed to evaluate the prognosis of spontaneous space closure and occlusion in uncontrolled permanent lower first molar extractions in patients with different developmental stages. Materials and Methods: Fifty permanent lower first molar extractions were included in the study. Extractions were divided into two groups as appropriate-timing (Group 1- 6th or 7th stages of Nolla) and late-timing (Group 2- 8th or 9th stages of Nolla), according to the Nolla calcification stage of permanent second molar germs in the same quadrant. In the 24th month, based on clinical/radiological/photographic data, the success of spontaneous space closure, rotation degrees of adjacent teeth, and dental midline deviations were evaluated. Results: Successful spontaneous space closure was observed in 52% in Group 1, and no successful result was present in Group 2. The difference was statistically significant (p<0.001). Rotation results of adjacent teeth were determined more frequently in Group 2, and the difference was not statistically significant (p=0.138, p=0.084, p=0.120). Dental midline deviations were statistically significantly higher in unilateral extractions compared to bilateral extractions (p=0.006). Conclusions: The timing of permanent lower first molar extractions for successful spontaneous space closure should be planned at the sixth or seventh development stage of the permanent lower second molar, according to Nolla's classification. Since rotations in adjacent teeth occur regardless of extraction timing, cases should be followed-up and intervened if necessary. Besides, unilateral permanent first molar tooth extractions should be avoided as much as possible since they cause dental midline deviation.